2020
DOI: 10.13057/biodiv/d210230
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of black pepper plant (Piper nigrum) in Bangka Island (Indonesia) based on agro-morphological characters

Abstract: Abstract. Prayoga GP, Aini SN, Mustikarini, ED, Rosalin Y. 2020. Diversity of black pepper plant (Piper nigrum L.) in Bangka Island (Indonesia) based on agro-morphological characters. Biodiversitas 21: 652-660. Black pepper (Piper nigrum L.) production in Bangka Belitung Islands Province continued to decrease in 2014-2017. Efforts to increase black pepper production was carried out by providing superior varieties that began with an increase in the genetic diversity of black pepper plants. Increasing the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Their study showed that yield of fresh pepper berries significantly negatively correlated with number of well-developed berries/spike, 100 berry weight and volume. Hence, selection programme based on these characters may likely not lead to the high yielding pepper variety compared to a selection based on of dry weight of pepper berries as dry weight of berries showed a negative significant genotypic correlation with number of berries/spike, 100 berry weight and 100 berry volume (Preethy et al 2018;Prayoga et al 2020). On the contrary, number of berries/spike has been reported as the most important morphological character that has direct and positive effect on pepper yield (Bermawie et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their study showed that yield of fresh pepper berries significantly negatively correlated with number of well-developed berries/spike, 100 berry weight and volume. Hence, selection programme based on these characters may likely not lead to the high yielding pepper variety compared to a selection based on of dry weight of pepper berries as dry weight of berries showed a negative significant genotypic correlation with number of berries/spike, 100 berry weight and 100 berry volume (Preethy et al 2018;Prayoga et al 2020). On the contrary, number of berries/spike has been reported as the most important morphological character that has direct and positive effect on pepper yield (Bermawie et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Observation and recording of morphological characters/descriptors has been a typical approach for identification and description of various pepper germplasms (Hussain et al 2017b;Bermawie et al 2019;Prayoga et al 2020). Other methods include pedigree, agronomic performance, biochemical and molecular/DNA-based data (Mohammadi and Prasanna 2003;Raghavan et al 2010;Deka et al 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in volatile compounds which make up essential oils were reported (Hao et al 2018;Dosoky et al 2019;van Ruth et al 2019). Lampung daun lebar, Jambi, and Merapin jumbo are local accessions of pepper that are widely cultivated in Kepulauan Bangka Belitung Province (Prayoga et al 2020). Therefore, in this study, it is suspected that there are differences in the profile of volatile compounds, characteristics, and antioxidant activity of these 3 (three) accessions.…”
mentioning
confidence: 77%